Characterization of biomass PM emissions using thermophoretic sampling: Composition and morphological description of the carbonaceous residues. (January 2019) - Patiño, David; Pérez-Orozco, Raquel; Porteiro, Jacobo; Lapuerta, Magín
Abstract: In this paper, a complete characterization of particulate matter (PM) emitted by a low-scale biomass combustor was performed. Samples were collected in three different zones of the installation (in-flame, boiler outlet and chimney outlet) using the thermophoretic sampling (TPS) method, and the different particle structures present in the biomass were studied from a chemical and a morphological point of view. Five types of particles were found: soot agglomerates, organic films, organic particles with imbibed fibrous structures, condensed tars and condensed inorganic salts. Transmission electron microscopy (TEM) was used for shape description, and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) was used for determining elementary composition. Specifically, soot agglomerates were submitted to a deeper characterization in terms of fractal descriptors, obtaining values for primary particle diameter, dpo, of 21.7 ± 8.4 nm, 21.4 ± 6.6 nm and 26.0 ± 5.9 nm for the three sampled zones, as well as values for fractal dimension, Df, between 1.40 and 2.60 and fractal prefactor, kf, between 2.20 and 2.40. The results were in agreement with other soot formation sources and showed an increasing tendency to cluster growth and compaction with the residence time inside the facility, being higher as they went further from the combustion zone. Fractal descriptors were not fairly influenced by the applied thermal treatment. Highlights: Morphology and composition of biomass PM families was performed using TPS sampling. The organic thin-film was the more frequent type and soot agglomerates were only 7%. dpo, Df and kf show soot's growth and compaction as a function of residence time. VOC's evaporation is fulfilled by the action of the TEM electron beam.